Exploring genetic information topics by using augmented reality in game-based learning / Siti Noor Syuhada Muhammad Amin ... [et al.] - Muhammad Amin, Siti Noor Syuhada; Mat Rosid, Salmiah Jamal; Abdul Malek, Azma; Mohammad Yusoff, Nurulhuda; Aziz, Siti Maisarah; Ismail, Ismahafezi (UiTM Cawangan Negeri Sembilan, 2023)
This study focuses on the development of an augmented reality learning tool in the game-based learning for the foundation Biology I (PAA 10104) course, along with its effects on student performance as well as their attitude towards the software. The student has the difficulty to learn and take more time to understand the subject. The aim of this study is to explore the impact of the tool on students’ cognitive performance and to gain an understanding of the various mechanisms and pathways of biological information expression. The results of the research will be used to determine the efficacy of the augmented reality software in teaching the subject matter. In this study, 85 students from UniSZA Science and Medicine Foundation Centre were involved. Augmented Reality interfaces are entirely based on the target user by applying a standard graphic user interface (GUI) in the virtual world. The students were instructed in answering the Nucleo-Beads boardgame’s survey and questionnaires. From the questionnaires, the feedback from student’s perceptions were analysed. The findings demonstrate that students' active involvement in hands-on activities has a particularly positive impact on their perception of enjoyment, which increases their motivation to learn. As a result, learning materials are seamlessly integrated into the environment around students in these augmented reality environments. Future research could investigate the impact by running experiments involving two or more student groups. Through game-based learning, this would give more insightful information on how to use augmented reality mobile applications.